2018
DOI: 10.1177/2055116917750763
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of Providencia rettgeri cholecystitis and neutrophilic cholangitis in a cat

Abstract: Case summaryA 15-year-old male neutered domestic shorthair cat was presented with a recent history of seizures, diarrhoea, lethargy, fever and jaundice. Marked elevation of liver enzyme activity was present and ultrasound examination was suggestive of cholecystitis and hepatitis. Neutrophilic cholangitis was confirmed on histopathology of liver biopsies. Bile culture identified a monomicrobial infection with Providencia rettgeri, which was resistant to multiple antimicrobial agents. The cat was treated with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…There is compelling evidence that bacteria are a primary impetus in the development of feline NC just as they are in humans with acute cholangitis. Bacteria are frequently cultured from bile, liver or both of cats with NC and even in their absence, a positive clinical response to antimicrobial therapy is noted (Hirsch & Doige 1983, Mayhew et al 2002, Brain et al 2006, Greiter-Wilke et al 2006, Wagner et al 2007, Mayhew & Weisse 2008, Callahan Clark et al 2011, Newton & Fry 2018. Further, a recent study identified bacteria within the livers of cats with NC with fluorescence in situ hybridisation (FISH) (Twedt et al 2014).…”
Section: Neutrophilic Cholangitis/ Cholangiohepatitismentioning
confidence: 99%
See 1 more Smart Citation
“…There is compelling evidence that bacteria are a primary impetus in the development of feline NC just as they are in humans with acute cholangitis. Bacteria are frequently cultured from bile, liver or both of cats with NC and even in their absence, a positive clinical response to antimicrobial therapy is noted (Hirsch & Doige 1983, Mayhew et al 2002, Brain et al 2006, Greiter-Wilke et al 2006, Wagner et al 2007, Mayhew & Weisse 2008, Callahan Clark et al 2011, Newton & Fry 2018. Further, a recent study identified bacteria within the livers of cats with NC with fluorescence in situ hybridisation (FISH) (Twedt et al 2014).…”
Section: Neutrophilic Cholangitis/ Cholangiohepatitismentioning
confidence: 99%
“…2011, Twedt et al . 2014, Newton & Fry 2018). Further, a recent study identified bacteria within the livers of cats with NC with fluorescence in situ hybridisation (FISH) (Twedt et al .…”
Section: Anatomy and Physiology Of The Biliary Systemmentioning
confidence: 99%